Virtual reality and augmented reality : 16th EuroVR International Conference, EuroVR 2019, Tallinn, Estonia, October 23-25, 2019, Proceedings /: 16th EuroVR International Conference, EuroVR 2019, Tallinn, Estonia, October 23-25, 2019, Proceedings. (2019) - Unknown
No abstract available